The Role of Self-Esteem in Foreign Language Learning and Teaching - Habrat, Agnieszka (Second Language Learning and Teaching,, 2018)
This book demonstrates how foreign language self-esteem (FLSE) affects foreign language (L2) learning and teaching, and how it fluctuates with growing proficiency. Further, it explains the interaction between FLSE and a range of factors of recognized importance in second language acquisition (SLA). The theoretical part of the book presents the main pillars of self-esteem as well as its notable influence on psychological functioning and learning, with special emphasis being placed on L2 learning. In turn, the empirical part presents the findings of a study that explored the trajectory and behavioural outcomes of FLSE across three stages of education. The book closes by outlining future research directions, as well as some pedagogical implications. In particular, the findings of the study can be employed in teaching English as a foreign or second language by helping instructors understand the significance of learners' individual differences.